DEMOCRACY IN ANGOLA AFTER THE CIVIL WAR (1975–2022):ANANALYSIS OF GOVERNMENT, POLITICAL PARTIES, AND PUBLIC INSTITUTIONS (REMUNOM, 2026)
The main objective of this paper is to briefly contextualize the challenges and advancements of democracy in Angola after the Civil War (1975-2022): an analysis of the government, political parties, and public institutions. This work aims to discuss the state of democracy and its developments during the post-independence period in Angola. The study was conducted using the bibliographic case study method and literature review. This approach revealed that the democratic fragility in Angola results in consequences such as lack of transparency, electoral justice, alternation of power, and credibility in public institutions factors that have instilled fear among the Angolan population, whose individual and collective freedoms are constantly threatened. Consequently, these contrasts in the political process hinder the construction of a sustainable democracy and a democratic state governed by the rule of law, with inclusive participation where all citizens feel committed to the future and the well-being of the entire Angolan population.